THE SYSTEMATIC REVIEW OF EXAMINING THE CONNECTION BETWEEN NUTRITION AND VERTIGO - Fitri Bumantari, Annisa; Ade Dewi, Fitri (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Aim : This study examined the association and connections between the uptake of nutrition and vertigo Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as uptodate as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and Science Direct, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done.  Result: In the PubMed database, the results of our search brought up 93 articles, whereas the results of our search on Science Direct brought up 163 articles. The results of the search conducted for the last year of 2014 yielded a total 67 articles for PubMed and 12 articles for Science Direct. In the end, we compiled a total of  4 papers, 2 of which came from PubMed and 2 of which came from Science Direct. We included four research that met the criteria. Conclusion: In summary, nutrient intake and consumption frequency of certain food categories varied significantly.